Simulations Of Two Bubbles Rise In Cavity With Lattice Boltzmann Method - Muhamad Zuhairi, Sulaiman (2008)

(untitled)
This paper explains the research work on two phase flow using Lattice Boltzmann Method. Three type of configuration of the bubbles simulation being simulated using Visual C++ program. Free energy model was reviewed then the base on latest models base on isotropy approach and Galilean invariance are also considered. Simulation results are validated and good agreement with previous studies.